Salivary stimulation by prolonged release of pilocarpine in Sjögren’s syndrome. - Rodríguez Pulido, Jesús Israel; Martínez Sandoval, Gloria; Rodríguez Franco, Norma Idalia; Chapa Arizpe, María Gabriela; Riega Torres, Janett Carmen Luzmila; Garza Elizondo, Mario Alberto (2017)
Abstract: Introduction: Prolonged drug delivery in the oral cavity offers many advantages, such as reducing adverse effects. Pilocarpine is an FDA-approved parasympathomimetic drug for the treatment of glandular hypofunction; however, its adverse effects limit its use. Objective: To evaluate the stimulation of salivary flow by the use of pilocarpine-releasing films, as well as their effects on the symptoms of xerostomia and adverse effects in patients with Sjögren’s syndrome (SS). Materials and methods: Hydroxypropylmethylcellulose (Methocel K4MCR) films were prepared in 1% acetic acid and pilocarpine was added under magnetic stirring. The pH and thickness, as well as diffusion uniformity and kinetics of drug release per cm2 were evaluated by spectrophotometry. The films were tested sublingually in 40 patients with Sjögren’s syndrome for a period of two weeks. Changes in their salivary flow were evaluated by analyzing samples of total saliva. Additionally, patients were screened for symptoms of xerostomia and adverse effects. Results: The films had a pH of 2.91±0.035, a thickness of 0.06866±0.00152μm, and a diffusion uniformity of 91% per cm2 . Use of the films resulted in an increase in salivary flow in both primary and secondary Sjögren’s syndrome, but this increase was only significant in primary SS. Conclusion: Films showed optimal physicochemical properties for their administration, and proved effective in stimulating salivary flow without causing adverse effects during their administration. Keywords: hyposalivation, Sjögren’s syndrome, pilocarpine, hydroxypropylmethylcellulose, xerostomia.